2003
DOI: 10.1159/000067890
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-Induced Cytotoxicity Involves Protein Kinase C Activation, Glutathione Extrusion and Malondialdehyde Production in an Immortalized Cell Line from the Organ of Corti

Abstract: The objective of the present study was to investigate the biochemical mechanisms underlying gentamicin cytotoxicity in OC-k3 cells derived from an immortalized cell line developed from the organ of Corti of transgenic mice. Administration of 50 µM gentamicin significantly reduced cell proliferation and viability, as well as initiating morphological changes associated with apoptosis. Protein kinase C (PKC) α activity was increased in gentamicin-treated cells, peaking 15 min after dosing (+138.2%). This PKCα inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…gentamicin, in contradistinction to cisplatin, has been shown to cause ototoxicity by formation of reactive oxygen species through the superoxide radical. The effects of gentamicin-induced reactive oxygen species in the organ of Corti explants are of increasing severity from the base to apex of outer hair cells (1). The sensitivity of basal turn hair cells has been linked to lower levels of glutathione as compared with levels of this antioxidant in the apex.…”
Section: Discussionmentioning
confidence: 99%
“…gentamicin, in contradistinction to cisplatin, has been shown to cause ototoxicity by formation of reactive oxygen species through the superoxide radical. The effects of gentamicin-induced reactive oxygen species in the organ of Corti explants are of increasing severity from the base to apex of outer hair cells (1). The sensitivity of basal turn hair cells has been linked to lower levels of glutathione as compared with levels of this antioxidant in the apex.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors described that GM in in vitro conditions decrease proliferation of human epidermal keratinocyte, probably through inhibition of transport RNA (Tekos et al, 2003[86]). Also GM inhibits cell proliferation in the organ of Corti and cells similar to human osteoblasts (Bertolaso et al, 2003[9]). The observed differences in GM effects on various cell is probably dependent on drug concentration as well as experimental conditions.…”
Section: Glomerular Effectsmentioning
confidence: 99%
“…In recent years, a variety of cephalosporins and quinolones have been widely used in clinics because of their longer post-antibiotic effects against Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli; however, aminoglycosides are used for the treatment of severe infections from aerobic gram-negative bacillus, including meningitis, trauma, burns and respiratory tract, urinary tract, skin soft tissue, joint and gastrointestinal tract infections (29). Previous studies have reported that the GM-induced hearing loss is associated with damage of cilia and hair cells (1,30). …”
Section: Discussionmentioning
confidence: 97%
“…Aminoglycosides are renowned antibiotics primarily used in clinics for the treatment of tuberculosis, and effectively cure infections caused by aerobic gram-negative bacteria (1)(2)(3). Gentamicin (GM) is a widely-used aminoglycoside antibiotic that has attracted increasing attention recently due to its potent ototoxic side effects.…”
Section: Introductionmentioning
confidence: 99%